The Effect of Electronic Performance Application and Work Skills on Employee Performance With Job Satisfaction as an Intervening Variable - Muchlis, Aditia; Prahiawan, Wawan; Lutfi, Lutfi (Sahabat Publikasi, 2025)
The purpose of this study is to test and analyze the impact of the application of electronic performance and work skills on employee performance with job satisfaction as an intervening variable. The research population consists of all civil servants in the DP3AKKB of Banten Province as many as 63 people using employee data in 2024. The sampling technique used is census sampling which involves collecting data from all relevant populations. Data was collected through a questionnaire followed by analysis using a quantitative method processed with SmartPLS software version 4. The results of the study show that performance electronics have a positive and significant effect on employee performance, work skills have a positive but insignificant effect on employee performance, performance electronics have a positive and significant effect on job satisfaction, work skills have a positive and significant effect on job satisfaction, satisfaction has a positive and significant effect on employee performance, job satisfaction is able to mediate electronic performance on performance employees, and job satisfaction are able to mediate work skills to employee performance.